2021
DOI: 10.15587/1729-4061.2021.225346
|View full text |Cite
|
Sign up to set email alerts
|

Development of a method for constructing linguistic standards for multi-criteria assessment of honeypot efficiency

Abstract: One of the pressing areas that is developing in the field of information security is associated with the use of Honeypots (virtual decoys, online traps), and the selection of criteria for determining the most effective Honeypots and their further classification is an urgent task. The main products that implement virtual decoy technologies are presented. They are often used to study the behavior, approaches and methods that an unauthorized party uses to gain unauthorized access to information system resources. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…The article [8] justifies and proves that the scientific task of providing the necessary level of protection of computer systems and networks from potentially dangerous cyber attacks requires the development of a new and effective method for constructing their templates. It is shown that the methodology for constructing patterns of potentially dangerous cyberattacks is rather complicated.…”
Section: Literature Review and Problem Statementmentioning
confidence: 83%
See 1 more Smart Citation
“…The article [8] justifies and proves that the scientific task of providing the necessary level of protection of computer systems and networks from potentially dangerous cyber attacks requires the development of a new and effective method for constructing their templates. It is shown that the methodology for constructing patterns of potentially dangerous cyberattacks is rather complicated.…”
Section: Literature Review and Problem Statementmentioning
confidence: 83%
“…From the Table 6 it is shown that the values of b k,11 (t n ), for k = 0 11 ... . Similarly, using (1) and the data in Table 5, let's obtain the initial analytical dependencies for the number of untested vulnerabilities q f = q f (t n ), ( 6) and the number of vulnerability testing cases that led to critical errors q c = q c (t n ), (7): 11 1 11t(1-t) 10 2 55t 2 (1-t) 9 3 165t 3 (1-t) 8 4 330t 4 (1-t) 7 5 462t 5 (1-t) 6 6 462t 6 (1-t) 5 7 330t 7 (1-t) 4 8 165t 8 (1-t) 3 9 55t 9 (1-t) 2 10 11t 10 (1-t)…”
Section: T T N ( )mentioning
confidence: 99%
“…The use of various noise-resistant codes makes it possible to ensure the required characteristics of both standard channels of information and communication systems and networks, and smart technology channels (wireless channels), as well as the transmission of various contexts (files, video, sound, etc.) [34][35][36][37][38][39]. In addition, the research carried out [1][2][3][27][28][29][30][31][32][33][34][35][36][37][38][39] makes it possible to use various algebrogeometric codes, LDPC codes with defective codes, which makes it possible to build hybrid crypto-code constructions and provide the required efficiency and strength of confidential cryptography.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
“…[34][35][36][37][38][39]. In addition, the research carried out [1][2][3][27][28][29][30][31][32][33][34][35][36][37][38][39] makes it possible to use various algebrogeometric codes, LDPC codes with defective codes, which makes it possible to build hybrid crypto-code constructions and provide the required efficiency and strength of confidential cryptography. The initial data for constructing such structures is the required parameters of durability and efficiency of transmitted information.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
“…На сьогодні, є досить ефективні розробки, які використовуються для вирішення завдань виявлення кібератак, наприклад, низка методів формування еталонних підсередовищ для СВВ [3][4][5][6][7][8][9] Для виявлення описаної кібератаки, далі, наприклад, за допомогою сервісів Phishtank -http:// phishtank.org/ (використовується для виявлення фішингових сайтів), Whois -https://who.is (використовується для визначення інформації про доменне ім'я сайту) та GeoIP -https://www.maxmind.com/en / geoip-demo (використовується для визначення місцезнаходження веб-сайтів) зберемо інформацію про 150 чистих та фішингових URLадрес за такими параметрами, як от «Кількість країн за IP-адресою» (за допомогою пінгового доменного імені отримаємо IP-адресу) та «Вік домену», який обчислюється за виразом ЗТД-СД=ТД, де ЗТД -дата закінчення терміну дії домену, СД -дата створення домену, ТД -термін дії домену. Отримані результати відповідних URL-адрес згрупуємо у таблицю 1.…”
Section: вступunclassified